Statistical analysis of waste generation in healthcare services: a case study - Eker, Hasan Huseyin; Bilgili, Mehmet Sinan (SAGE PUBLICATIONS LTD, 2011)
In the present study, the amounts of medical waste materials, sharps, liquid waste, hazardous waste, household waste and recyclables generated from 375 healthcare services including private hospitals, state hospitals, university hospitals, private medical centres, dialysis centres, cottage hospitals and private dentist surgeries were determined, and the relation between the amount of the waste and the bed capacities, inpatient and outpatient numbers were evaluated. The amount of regulated medical waste corresponded to 28.8% of the total waste streams collected from the healthcare services, and the major producers were private hospitals. The major producers of hazardous waste were state hospitals with a generation rate of 57.9%. The main results of the study indicate that the quantities of the waste streams generated from healthcare services in accordance with the outpatient number gave more appropriate results than the other evaluation methods. Furthermore, evaluation based on the bed capacities gave reasonable results except for recyclables and hazardous waste. As a result of the evaluation of the medical waste generation rate with bed capacities, the generation rate was determined as 2.11 +/- 3.83 kg bed(-1) day(-1) and this rate was 1.45 +/- 9.84 kg outpatient(-1) day(-1) for the evaluation by outpatient numbers. The observed significant P values (P > 0.05) indicate that the evaluation of the waste streams in healthcare services based upon outpatient numbers did not show any reasonable change according to service category.
Keywords: Healthcare service; medical waste; generation rate; statistics; MEDICAL WASTES; MANAGEMENT-PRACTICES; JORDAN; HOSPITALS; PROVINCE; TURKEY; IRAN; Engineering; Environmental Sciences & Ecology